HUBUNGAN KOMPETENSI PROFESIONAL DENGAN KINERJA GURU (Survei pada guru bersertifikat di Madrasah Aliyah ATTAQWA 04) - Iqlima Sajidah; Yayat Suharyat (Turats, 2020)
Teacher performance certification at Madrasah Aliyah At-Taqwa 04 Bekasi is very important torealize because it determines the achievement of national education goals. The purpose of this studyis to examine the relationship between teacher professional competence and teacher performance atMA At-Taqwa 04 Bekasi City. The main problem in this study is to get an idea of how professionalcompetence and teacher performance certification are the main problems that will be described inthe results of this study. The research method used is quantitative with descriptive analysis. Whilethe data collection techniques include questionnaires, interviews, and observations. The populationin this study were Islamic religious education teachers totaling 20 people with a sample of 20 peopledetermined through saturated sampling techniques. The data analysis was carried out quantitativelyand the hypothesis was tested using the r test formula. The results of this study concluded that thecompetence of teachers was good. Likewise, the teacher's performance is quite good. While therelationship between the influence of professional competence of teachers with teacher performancecertification obtained a value of 0.680 and means at a significant level of 0.05. Thus, the two variables,namely variable X, namely professional competence, and variable Y, the performance of certificationteachers are positively related, meaning that the better the professional competence of teachers, thebetter the performance of certified teachers at MA At-Taqwa 04 Bekasi City.